Penilaian Dan Optimalisasi Konfigurasi Rekahan Hidraulik Sumur “HE-04” di Lapangan “S” - Dharma Arung Laby; Abdi Suprayitno; Amiruddin; Aprilno Alfa Kumasela; Hizkia Erick Sualang; Darmiyati, Iin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
Well “HE-04” in Field “S” is a hydrocarbon production well located in a reservoir with relatively low permeability, measured at 10.80 mD. This low permeability results in a low productivity index (PI). To enhance well productivity, hydraulic fracturing was performed to create conductivity between the reservoir and the wellbore, with the objective of increasing the PI. Hydraulic fracturing involves injecting fluid at high pressure to create fractures in the formation, followed by the placement of proppant to keep the fractures open. However, post-fracturing results indicated that the dimensionless fracture conductivity (FCD), which represents the fracture conductivity, remained low. Therefore, evaluation and optimization of the fracture geometry are necessary to achieve optimal conductivity and improve PI. This study evaluates the PI using the Prats method and optimizes the fracture geometry by redesigning the initial fracture using the Unified Fracture Design (UFD) method within the Perkins-Kern-Nordgren (PKN) geometry model. The process begins with an evaluation of the actual PI, followed by redesigning the fracture geometry to determine the maximum fracture dimensions. This maximum geometry is then optimized using the UFD method to obtain the most effective geometry. The optimization results show that the maximum fracture volume that can be generated is 685.51 m³, with a resulting FCD value of 8.37. The fold of increase (FOI) reached 8.54, an improvement of 5.43 compared to the actual FOI. This indicates that the optimized PI increased by 8.54 times from its initial value. Thus, the optimized fracture geometry design proves to be effective in enhancing the productivity of well “HE-04”.